Estimates of the extinction probability of the Galton-Watson process - Goryainov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We generalize Quine's result on the convergence of the extinction probability of the supercritical Galton-Watson process to one if the average number of offsprings tends to one without any restrictions on factorial moments.